Yamuna Action Plan-III: Impact on Water Quality of River Yamuna, India - Ankit Srivastava; Prathna T.C. (Fine Chemical Engineering, 2021)
Water is indispensable to sustain life and livelihood, and rivers serve as major reservoirs of water in manyparts of the world. River Yamuna is the major tributary of the River Ganges in India and is considered to be among the most polluted rivers of the world. The Yamuna Action Plan (YAP) is one of the largest river restoration projects in India and is initiated to clean the river. YAP is a bilateral arrangement between the governments of India and Japan, and consists of three Actions Plans-I, II and III. YAP-III is currently under execution with some of the major projects being the construction of the new Wastewater Treatment Plant (WWTP) at Okhla, rehabilitation and upgrading of WWTPs at Kondli and Rithala in the Delhi region. The impact of YAP-III with regard to these major projects on the reduction of the pollutant load reaching the river and cost-benefit has been evaluated in the current study. Findings from the study indicated that major projects such as construction of a new WWTP at Okhla (124 MGD) can effectively reduce the pollutant load by 283 kg/MGD of wastewater at a cost of Rs. 1161 crores while the rehabilitation project at Rithala (Phase I) can reduce the pollutant load by 92.5 kg/MGD wastewater at a cost of Rs. 300 crores. The present study indicates the need to evaluate projects in terms of cost-benefit analysis in addition to the economic and environmental evaluation for effective action. A holistic approach towards treatment of pollutant load in the river and prevention of further pollutants from reaching the river is required in addition to community awareness and participation for sustainable river water management.